MIND MAPPING AS AN EFFECTIVE WAY OF TEACHING YOUNG LEARNERS - Bekbergenova Gulayim Ayjarikovna,; Tolibaeva Kamila Timurovna, (TADQIQOTLAR, 2026)
Abstract: Mind mapping is a powerful educational tool that has gained significant attention in recent years, particularly in the context of teaching young learners. Its visual approach, which relies on diagrams and illustrations to organize information hierarchically, appeals to the natural ways children acquire and process knowledge. This  technique  not  only  simplifies  complex  information  but  also  fosters  creativity, enhances memory, and supports a variety of learning styles. In the setting of early education, where traditional linear note-taking may be less effective due to children’s developmental stages, mind mapping emerges as an adaptive and innovative strategy.